"Students at risk:" A practitioner-based approach to noncompletion in adult education - LeDeane R. Jha; John M. Dirkx (Adult Education Research Conference, 1994)
The primary purpose of this study was to statistically assess the efficacy of an instrument designed by a task force of program teachers, volunteers, administrators and researchers to prospectively differentiate completing from noncompleting students in adult basic education. Three broad groups of enrollment patterns were identified and analysis of variance demonstrated statistically significant difference among these three groups. Post hoc analysis found significant difference between the mean number of risk factors identified for completing and noncontinuing students. In addition, potentially important practical differences were found among outcome of enrollment groups on ten of the fourteen "risk factors".